Efektivitas Media AKUBERANI: Edukasi Visual Interaktif Bagi Anak Tunagrahita Ringan Mengenai Batasan dan Persetujuan Tubuh - Syafril, Muthia; Rochyadi, Endang; Aprilia, Imas Diana (Universitas Negeri Padang, 2025)
Mildly disabled children often experience barriers in understanding the concept of bodily boundaries and consent, which impacts their vulnerability to the risk of rights violations and sexual violence. This study aims to develop and test the effectiveness of augmented reality-based learning media AKUBERANI as an interactive visual educational media to improve mildly disabled children's understanding of body boundaries and consent. The research method used is a mixed method with an exploratory design. The research subjects were four children with mild impairment in phase D at SLB Negeri Duri. Data were collected through observation, interviews, expert validation, and tests of children's understanding abilities before and after using the media. The analysis showed a significant increase in children's understanding after using augmented reality